Management of patients with acquired valvular heart disease in noncardiac surgery - O. B. Irtyuga; E. G. Malev; M. L. Gordeev (Российский кардиологический журнал, 2021)
Valvular heart disease is widespread among general population, mainly in older age groups, who often require noncardiac surgery. As the population ages, the significance of this problem will only increase. The basic principles of perioperative managing such patients by a multidisciplinary team, necessarily including a cardiologist, are systematized and set out in international clinical guidelines, which are regularly updated. Currently, the Russian Society of Cardiology guidelines on management of valvular heart diseases are being prepared for publication. However, specifics of assessment and management of patients when planning noncardiac surgery require more detailed presentation for a cardiology practitioner.